Corporate Management in a Knowledge-Based Economy - Zanda, G.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
Corporate Management in a Knowledge-Based Economy traces the evolution of corporate governance over time, with a particular focus on the changing nature of power. The control of scarce resources used in production materials, labour and capital has evolved considerably over the past centuries, with government, landowners, non-owner managers, and institutional investors acting as controlling powers at different points in time. In order to appropriately protect the various, and changing, stakeholders, the system of corporate governance has also developed over the years a process that continues to the present. In today's knowledge-based economy, with the rising importance of intangible assets, a new corporate management paradigm is needed. This book incorporates theoretical work as well as practical applications to analyse these developments and explore emerging trends of the 21st century. It examines how the pursuit of profit maximization has resulted in governance failures and it focuses on the prospective role of business ethics (once again in the spotlight following the credit crisis) in helping reform flawed governance structures. It argues that, in the long term, a system based on ethics can maximize social responsibility, customer satisfaction, human capital development and economic targets.
Keywords: Business enterprises—Finance.; Leadership; Corporations—Finance.; International business enterprises; Management; Personnel management; Business Finance; Business Strategy/Leadership.; Corporate Finance; International Business; Management; Human Resource Management